Anterior Cervical Microdiscectomy and Fusion: A Single Center Study with Management and Outcomes - Encarnacion Santos , Daniel; Pachev , Murat; Shestov , Eugeny; Bozkurt, Ismail; Jimenez-Alvarez , Jorge; Fuente-Hernandez , Jose de la; Chmutin, Gennady; Chmutin, Egor; Chaurasia, Bipin; Yangi, Kivanc (Eastern Green Neurosurgery, 2026)
Background: Cervical spondylosis surgery can be performed through two primary approaches: anterior and posterior. The initial anterior approaches were reported by Robinson and Smith in the mid-1930s, followed by Cloward (1958). The aim, based on the placement of the cage within the intervertebral space and the stabilization offered by the plate, was assessed to determine its impact on enhancing postoperative cervical spine dynamics.Materials and Methods: A retrospective cohort study was undertaken on 21 patients (9 male and 11 female) in the age range of 28 to 66 years old to explore variations in postoperative outcomes among patients who underwent anterior cervical microdiscectomy and fusion with a cage. The research was done between January 2023 and November 2024.Results: We performed a retrospective observational analysis of N=20 patients who matched our inclusion criteria, and we included 9 men and 11 females, aged between 28 and 66 years, with N=7 patients with left radiculopathy for (35%) and N=10 patients with right radiculopathy for (50%). while N=3 patients exhibited symptoms of radiculopathy or numbness. (15%).Conclusion: In our study, the position of the cage in the intervertebral space and the fixation supplied by the plate were analyzed to assess their impact on improving the dynamics of the postoperative cervical spine. The postoperative outcomes include reduction of the C6 vertebral dislocation and anterior cervical fusion at C6-C7 utilizing the IRENE cage.